2015
DOI: 10.1111/ldrp.12054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the SOLVE Strategy on the Mathematical Problem Solving Skills of Secondary Students with Learning Disabilities

Abstract: This study examined the effects of explicit instruction in the SOLVE Strategy on the mathematical problem solving skills of six Grade 8 students with specific learning disabilities. The SOLVE Strategy is an explicit instruction, mnemonic-based learning strategy designed to help students in solving mathematical word problems. Using a multiple probe across participants design, results suggested a functional relation between explicit instruction in the SOLVE strategy and increase in strategy use and computation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 36 publications
3
44
0
2
Order By: Relevance
“…IP focuses on general processes in mathematics learning, not on specific mathematical content areas. Strategic instruction, a major aspect of information processing, has researched the general heuristics through which students solve word problems [21]. According to a review of IP research [18], IP typically uses experimental quantitative methodologies to understand human processing.…”
Section: Historical Roots Of Mathematics Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…IP focuses on general processes in mathematics learning, not on specific mathematical content areas. Strategic instruction, a major aspect of information processing, has researched the general heuristics through which students solve word problems [21]. According to a review of IP research [18], IP typically uses experimental quantitative methodologies to understand human processing.…”
Section: Historical Roots Of Mathematics Educationmentioning
confidence: 99%
“…By following and demonstrating these processes, students learn to solve problems successfully. For example, Freeman-Green et al [21] (2015) described an intervention using a scripted problem solving routine called SOLVE. They found that explicit instruction in this problem solving routine was effective in increasing the problem solving skills of six secondary students with learning disabilities.…”
Section: Behavioral Theoretical Orientationmentioning
confidence: 99%
“…The ability to solve problems will be achieved optimally if it is balanced by the presence of positive characters in the students. Some character values which need to be possessed by the students in this case are honesty, perseverance, not easy to give up, democratic and able to work together (Freeman Green, O'Brien, Wood -& Hitt, 2015;Rokhman et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…By following and demonstrating these processes, students learn to solve problems successfully. For example, Freeman-Green, O'Brien, Wood, and Hitt [21] (2015) described an intervention using a scripted problem solving routine called SOLVE. They found that explicit instruction in this problem solving routine was effective in increasing the problem solving skills of 6 secondary students with learning disabilities.…”
Section: Behavioral Theoretical Orientationmentioning
confidence: 99%
“…In general, IP focuses on general processes in mathematics learning, not in specific mathematical content areas. Strategic instruction, a major aspect of information processing, has researched the general heuristics through which students solve word problems [21]. According to a review of IP research [18], IP typically uses experimental quantitative methodologies to understand human processing.…”
Section: Historical Roots Of Mathematics Educationmentioning
confidence: 99%